Zebrafish as an animal model for drug discovery in Parkinson's disease and other movement disorders - Vaz, Rita L. (2018)
The authors would like to thank Mariana Trigo Pereira, who kindly provided the pictures of zebrafish. RV was supported by a grant (SFRH/BD/78077/2011) from Fundação para e a Ciência e Tecnologia. TO is supported by the DFG Center for Nanoscale Microscopy and Molecular Physiology of the Brain (CNMPB).